2020
DOI: 10.1007/s11244-020-01324-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structure–Activity Relationship on Platinum Nanoparticles

Abstract: The design of active and stable Pt-based nanoscale electrocatalysts for the oxygen reduction reaction (ORR) plays the central role in ameliorating the efficiency of proton exchange membrane fuel-cells towards future energy applications. On that front, theoretical studies have contributed significantly to this research area by gaining deeper insights and understanding of the ongoing processes. In this work, we present an approach capable of characterizing differently-shaped platinum nanoparticles undergoing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…This observation highlights the importance of taking both geometrical and electronic effects into account when studying reactivity trends in catalysis. 34 Beyond the clean particle, surface oxide, and fully oxidized ([Pt 6 O 8 ] n ) phases in the electrochemical phase diagrams, a fourth phase representing the bulk oxide, α-PtO 2 , would technically be expected. Note that α−PtO 2 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This observation highlights the importance of taking both geometrical and electronic effects into account when studying reactivity trends in catalysis. 34 Beyond the clean particle, surface oxide, and fully oxidized ([Pt 6 O 8 ] n ) phases in the electrochemical phase diagrams, a fourth phase representing the bulk oxide, α-PtO 2 , would technically be expected. Note that α−PtO 2 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, force fields typically fail to describe bond-breaking and bond-making processes. Reactive force fields based on bond-order concepts are free from this restriction, but they require a considerable fitting effort and are therefore typically restricted to a small number of elements. , On the other hand, interpolation schemes including many-body effects such as the embedded atom method (EAM) , are appropriate for simple metals but cannot appropriately reproduce covalent bonding.…”
Section: Theoretical Description Of the Water–water And Water–metal I...mentioning
confidence: 99%
“…They showed that such metal-adsorbate interactions diminish the nanoparticles' thermal stability against solid-solid and solid-liquid transitions. Similarly, Braunwarth et al [43] observed the long-term stability of Pt cubes solvated in water by means of a ReaxFF potential. The cubes underwent a strong restructuring into concave disordered cuboids after a few ns of simulation.…”
Section: Catalyst-solvent Interfacementioning
confidence: 84%